2016
DOI: 10.1016/j.bjorl.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and endoscopic characteristics of acute laryngeal lesions in children undergoing endotracheal intubation

Abstract: Most children in the study developed mild acute laryngeal lesions caused by endotracheal intubation, which improved in a few days after extubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
15
0
4
Order By: Relevance
“…However, it requires the patient to be exposed to general anesthesia, which may not be the best approach for a critically ill child who is recovering from a major illness De Lima et al, however, have preferred bedside examination with the help of flexible scope in awake patients. [14] Smith et al, in a study on 41 children in a PICU, noted that flexible laryngoscopy can be performed safely with a few minor complications. [15] They also concluded that laryngoscopy can be done easily with good visualization of all regions of the larynx, including subglottis.…”
Section: Discussionmentioning
confidence: 97%
“…However, it requires the patient to be exposed to general anesthesia, which may not be the best approach for a critically ill child who is recovering from a major illness De Lima et al, however, have preferred bedside examination with the help of flexible scope in awake patients. [14] Smith et al, in a study on 41 children in a PICU, noted that flexible laryngoscopy can be performed safely with a few minor complications. [15] They also concluded that laryngoscopy can be done easily with good visualization of all regions of the larynx, including subglottis.…”
Section: Discussionmentioning
confidence: 97%
“…Subglottic stenosis is a complication that frequently develops after intubation and is characterized by respiratory distress . The aim of this study was to investigate the demographic features and risk factors associated with the development of SGS in intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Subglottic stenosis (SGS) is one of the most common causes of upper airway obstruction in childhood. It can be congenital or acquired and has a frequency between 0.6% and 11% …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Una laringoscopía inadecuada puede exponer el pecíolo epiglótico y promover el daño a nivel de la comisura anterior. En el caso del daño por presión, las zonas más afectadas son la cara medial de los aritenoides, la comisura posterior (debido a la ubicación del tubo en la laringe) 2 y la subglotis (pues es el punto más estrecho y menos distensible de la laringe pediátrica) 3 . La incidencia de lesiones isquémicas traqueales asociadas al cuff han disminuido considerablemente gracias al uso de balones de alto volumen y baja presión, que permitirían mantener un sello adecuado en la vía aérea sin superar la presión de perfusión capilar de la mucosa traqueal 4 .…”
Section: Introductionunclassified